Biodegradable herbicide delivery systems with slow diffusion in soil and UV protection properties - Chevillard, Anne; Angellier‐Coussy, Hélène; Guillard, Valérie; Bertrand, Cédric; Gontard, Nathalie; Gastaldi, Emmanuelle (Pest management science, 2014)
BACKGROUND: New herbicidal formulations were designed by combining wheat gluten (WG), two montmorillonites (MMTs) (unmodified and organically modified) and a model pesticide (ethofumesate), and their performances were assessed through an integrative study conducted in soil using an experimental methodology with data modelling. RESULTS: All the WG formulations tested were effective in decreasing the apparent diffusivity of ethofumesate in soil in comparison with the non‐formulated active substance. The slow‐release effect was significantly more pronounced in the presence of the organically modified MMT, confirming the importance of sorption mechanisms to reduce ethofumesate diffusion. The bioassays undertaken on watercress to evaluate herbicidal antigerminating performances showed that all the WG formulations (with or without MMT) were more effective than both the commercial formulation and the non‐formulated ethofumesate, whatever the concentration tested. To explain such results, it was proposed that WG formulations would enable ethofumesate to be more available and thus more effective in inhibiting seed germination, as they would be less prone to be leached by water transport due to watering and also less subject to photodegradation. CONCLUSION: The use of pesticide formulations based on wheat gluten and nanoclays appeared to be a promising strategy both to reduce the mobility of pesticides in soil and to protect UV‐photosensitive pesticides from photodegradation. © 2013 Society of Chemical Industry